2018
DOI: 10.1159/000487978
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of PRKAR2B Results in the Failure of Oocyte Maturation

Abstract: Background/Aims: Cyclic adenosine monophosphate (cAMP)-dependent type 2 regulatory subunit beta (Prkar2b) is a regulatory isoform of cAMP-dependent protein kinase (PKA), which is the primary target for cAMP actions. In oocytes, PKA and the pentose phosphate pathway (PPP) have important roles during the germinal vesicle (GV) stage arrest of development. Although the roles of the PKA signal pathway have been studied in the development of oocyte, there has been no report on the function of PRKAR2B, a key regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…There are four different regulatory subunits (RIα, RIβ, RIIα and RIIβ) of PKA in human mammalian tissues 7 . Protein kinase cAMP‐dependent regulatory type II beta (PRKAR2B) plays a role in oocyte maturation, 8 regulates murine and human adipocyte differentiation 9 and inhibits the effect of cAMP responsive element binding protein (CREB) activity in T cells 10 . Recently, we identified PRKAR2B as a novel oncogene implicated in the development of CRPC 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…There are four different regulatory subunits (RIα, RIβ, RIIα and RIIβ) of PKA in human mammalian tissues 7 . Protein kinase cAMP‐dependent regulatory type II beta (PRKAR2B) plays a role in oocyte maturation, 8 regulates murine and human adipocyte differentiation 9 and inhibits the effect of cAMP responsive element binding protein (CREB) activity in T cells 10 . Recently, we identified PRKAR2B as a novel oncogene implicated in the development of CRPC 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…5 ) [ 1 , 51 , 52 ]. In this study, we found, for the first time, that the expression of RAB5B [ 53 ] which promotes the degradation of damaged mitochondria was decreased, the expression of PPP2R2A [ 54 ] which represses BAX, and the expression of PRKAR2B [ 55 , 56 ] which represses BAX via the pentose phosphate pathway were decreased in the cerebral blood vessels of ADNC +/CAA + patients (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 81%
“…during oocyte metabolism ( 61 ). Similarly, the expression of PRDX2 in external vesicles has been suggested as a predictor of embryo implantation ability ( 62 ), while RFX1 and PRKA2 were related to embryonic development failure and lethality in mice ( 63 , 64 ). The fact that none of these genes were mentioned as pivotal infertility processes suggests that they may be involved in the modulation of fertility in mares by a polygenic pathway, via small genetic effects ( 11 ).…”
Section: Discussionmentioning
confidence: 99%